2021
DOI: 10.17930/agl202111
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW ON KNOWLEDGE GAP IN Brachiaria GRASS RESEARCH AND UTILIZATION: ETHIOPIAN PERSPECTIVE

Abstract: Still food security has not been attained fully in many tropical African countries including Ethiopia. However, the issue of food security achievement has been able to realize due to various setbacks among which low productivity of crops and livestock take the lion share. Among the various constraints the parasitic weed Striga, and Stemborer pests are responsible for lower crop yields in the region. Regarding livestock feed, shortage in terms of quantity and quality are the major impediment to the livestock se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
3
6
1
Order By: Relevance
“…The significant increase in plant height observed by plants treated with the highest rate of fertilizer level and increased age of plants could be due to an adequate supply of fertilizer that might promote the formation of chlorophyll that in turn resulted in higher photosynthetic activity, vigorous vegetative growth, and taller plants and as the age of plants increased the wellestablished root development and nutrient uptake ability of the grasses which in turn could be manifested by the increment of plant height and leaf length. The result of this finding agrees with the previous finding of [23,24] who reported that the plant height of Brachiaria grass significantly increased as the harvesting stage increased from 60 to 120 days in northwestern Ethiopia. The mean value (69.47 cm) of PH obtained in this study was higher than the earlier finding of [24] which was 28.63 cm for Brachiaria hybrid Mulato II grass in Northwestern Ethiopia.…”
Section: Lant Height At Harvest (Ph)supporting
confidence: 92%
See 4 more Smart Citations
“…The significant increase in plant height observed by plants treated with the highest rate of fertilizer level and increased age of plants could be due to an adequate supply of fertilizer that might promote the formation of chlorophyll that in turn resulted in higher photosynthetic activity, vigorous vegetative growth, and taller plants and as the age of plants increased the wellestablished root development and nutrient uptake ability of the grasses which in turn could be manifested by the increment of plant height and leaf length. The result of this finding agrees with the previous finding of [23,24] who reported that the plant height of Brachiaria grass significantly increased as the harvesting stage increased from 60 to 120 days in northwestern Ethiopia. The mean value (69.47 cm) of PH obtained in this study was higher than the earlier finding of [24] which was 28.63 cm for Brachiaria hybrid Mulato II grass in Northwestern Ethiopia.…”
Section: Lant Height At Harvest (Ph)supporting
confidence: 92%
“…Similarly, [28,32,36,37] reported the highest DMY that was produced from cultivated grasses and natural pastures as harvesting stages were delayed. The TDMY 16.43 t/ha obtained from two harvests in this study is higher than the finding of [24,26] which were 10.38 t/ha and 9.18 t/ha from Brachiaria Mulato II grass in Ethiopia. Similarly, it is also higher than the earlier result of [38] which was 8.30 t/ha in Rwanda.…”
Section: Total Dry Matter Yield (Tdmy)contrasting
confidence: 80%
See 3 more Smart Citations